IMPLEMENTASI QUICK RESPONSE CODE UNTUK PENDUKUNG SISTEM INFORMASI PRESENSI - Nur Indah Kusumawardhani; Ika Nur Fajri (Universitas Gunadarma, 2024)
The development of science and technology (IPTEK) and information is a reality that must be faced by everyone, including educational institutions and government agencies. One example is the use of information technology in schools to facilitate the work of educators and education personnel. However, in primary, secondary, and higher education, many still use manual attendance. SMK Negeri 2 Klaten also experienced this problem. To overcome this problem, a website was designed to record, report, and monitor student attendance using the QR Code scanning method. This research uses the waterfall method which includes Requirements Analysis, System Design, Implementation, Integration and Testing, and Operation and Maintenance. The results showed that a website-based attendance information system can speed up and simplify the attendance process, reduce errors, and increase efficiency. It is proven that after testing the QR Code based on the scanning distance, the scanning response speed only requires a delay of 0.94 seconds at an effective distance of 20 cm. In conclusion, the application of information technology in the attendance process at SMK Negeri 2 Klaten can improve the quality and efficiency of attendance management.